EXPLOSIVE NUCLEOSYNTHESIS AT STRONG STELLAR MAGNETIZATION - Kondratyev, V. N.; Korovina, Yu. V. (Одеські астрономічні публікації, 2014)
Synthesis of iron group nuclides is considered for the ultra-magnetized astrophysical plasma in supernovae. Magnetic modification of nuclear structure is shown to shift maximum of nucleosynthesis products towards smaller mass numbers enhancing titanium yield. The results are corroborated with an excess of 44Ti revealed from the INTEGRAL mission data for yang supernova remnants at a field strength ranging up to 10 teratesla.